Development of microbubbles - Lim, Jing Yi (2017)
Magnetic microbubbles have always been a research trend in recent years due to its growing number of purposes in therapeutic researches such as ultrasound contrast agent as well as drug and gene delivery. The microbubbles are utilized more in drug delivery due to its ability to contain drug in a bubble, has low leakage rate and high accuracy in releasing the drug at desired part in the body. For example, Stuart I. el at. have reviewed on the potential of microbubbles of becoming a treatment replacement for chemotherapy, a treatment which is very harmful to living cells in a human body to kill cancerous cell. Therefore, instead of going through pain in the whole process, drug-encapsulated microbubbles can be used to deliver drug to the cancerous cell. The diameters of the magnetic microbubbles must be below 8μm in biomedical applications as the upper limit of diameter of capillaries (the smallest blood vessel group) is approximately 10μm. After understanding the purpose of magnetic microbubbles in therapeutic applications, the objectives of the projects are: 1. To develop magnetic microbubbles. 2. To size the magnetic microbubbles with diameters of 8μm and below to study for biomedical applications. 3. To characterize the magnetic microbubbles by determining the acoustic properties under ultrasound test and its behaviour under the influence of magnetic field. The preparation of magnetic microbubbles is referred from the research projects done by Soetanto K el at. and Gao Y. el at. Both methods have different approaches, where one is utilizing of multivalent ions and performing electrostatic coupling and the other is to disperse iron (II,III) oxide nanoparticles with sonication and encapsulating the microbubbles with highspeed agitation. To conduct ultrasonic testing, there are two types of thresholds to determine before carrying the test. Firstly, the fragmentation threshold, also known as stable fragmentation, is first determined by increasing 20mV for an interval of 10 seconds. The highest peak will be recorded and averaged. The stable fragmentation, which produces low ultrasound intensity, manipulates the microbubbles. The inertial cavitation is also determined for the collapse of microbubbles. A permanent magnet is used to observe the behaviour of the magnetic microbubbles. Next, experiments are conducted at a fixed input signal over a duration of 30 seconds to further determine the pressure threshold. ii Throughout the whole project, two out of three objectives have been achieved. Despite that, there are many limitations faced throughout the project and various recommendations are made in the report.